Identification of a low frequency missense mutation in MUC6 contributing to pulmonary artery hypertension by whole‐exome sequencing. (1st August 2018) - Zou, Lihui; Li, Wenqing; Han, Jingli; Yang, Yuanhua; Jin, Junhua; Xiao, Fei; Xu, Xiaomao; Zhai, Zhenguo
Abstract : Pulmonary arterial hypertension (PAH) represents a progressive disease characterized by abnormally high blood pressure in the pulmonary artery. Although mutations in the bone morphogenetic receptor 2 (BMPR2) are found in 80% of heritable, their low penetrance suggests that other unidentified genetic modifiers are required for this disease. In this report, whole‐exome sequencing (WES) and a linkage analysis were performed on genomic DNA isolated from four affected relatives and one non‐affected relative in two PAH families. By focusing on meaningful variants which were presented in the four affected family members, but not presented in the non‐affected individual, 49 SNP and eight indel variants in 39 genes were identified as candidates. Further high‐throughput multiplex genotyping and Sanger sequencing were carried out to confirm the putative causal mutations in 150 individuals (30 idiopathic PAH [IPAH] patients, 30 chronic thromboembolic pulmonary hypertension [CTEPH] patients, and 90 normal controls). A heterozygous and deleterious mutation in the gene MUC6 (p.Pro1716Ser) was confirmed in the IPAH group (20/30, 67%) and CTEPH group (1/30, 3.33%); no variant was detected in the 90 normal controls. MUC6, which is short for mucin 6, encodes high molecular weight glycoprotein produced by many epithelial tissues and forms an insoluble mucous barrier that protects the lumens. We re‐confirmed this low frequency mutation with the 1000 Genomes database across all species; no population or frequency data of this allele were acquired. We also found that this mutation site was highly conserved in different species and predicted MUC6 has the protection function of the airway and pneumoangiogram based on genomic sequence data. The compound heterozygous MUC6 gene mutation (p.Pro1716Ser) suggests a novel disease mechanism leading to PAH.